Glacial/interglacial changes of Southern Hemisphere wind circulation from the geochemistry of South American dust - Gili, Stefania; Gaiero, Diego Marcelo; Goldstein, Steven L.; Chemale, Farid; Jweda, Jason; Kaplan, Michael R.; Becchio, Raul Alberto; Koester, Edinei (Earth and Planetary Science Letters)
The latitudinal displacement of the southern westerlies and associated climate systems is a key parameter for understanding the variations of Southern Hemisphere atmospheric circulation during the Late Quaternary Period. To increase understanding of past atmospheric circulation and of the paleo-environmental conditions associated with continental dust sources, we dig deeper into dust provenance in paleo-archives of the Southern Hemisphere. We present here a Sr?Nd isotopic and rare earth element study of surface sediments collected along a ∼4000 km latitudinal band from arid and semi-arid terrains in southern South America. Findings from terrains that served as paleo-dust suppliers are compared with modern dust collected from monitoring stations along the same latitudinal band, which affords a test on how actual present-day aeolian compositions compare to those of the past potential source areas. Moreover, the comparison between past and present-day datasets is useful for understanding present-day atmospheric circulation. Armed with a new comprehensive dataset, we revise previous interpretations of the provenance of dust trapped in the Antarctic ice and sediments deposited in the South Atlantic sector of the Southern Ocean. These comparisons support multiple source regions in southern South America that changed with climates. The findings reveal that, although Patagonia plays an important role in contributing dust to the higher latitudes, central Western Argentina and (to a lesser extent) the southern Puna region also emerge as potentially important dust sources during glacial times. The southern Altiplano appears to be a major contributor during interglacial periods as well. We rely in part on an understanding of modern wind?dust activities to conclude that the possible presence of southern South America source regions ? other than Patagonia ? in East Antarctic ice is consistent with an overall equatorward displacement during glacial times of both the mid-latitude westerlies and the subtropical jet stream. ...